A Satellite‐Based Estimate of Convective Vertical Velocity and Convective Mass Flux: Global Survey and Comparison With Radar Wind Profiler Observations. Issue 1 (9th January 2021) - Jeyaratnam, Jeyavinoth; Luo, Zhengzhao Johnny; Giangrande, Scott E.; Wang, Dié; Masunaga, Hirohiko
Abstract: Convective vertical velocity ( w c ) and convective mass flux ( M c ) lie at the heart of global climate model cumulus parameterizations, but few observations of these critical parameters are available. This paper develops and evaluates a novel, satellite‐based method for estimating profiles of w c and M c . Comparisons with collocated ground‐based radar wind profiler (RWP) observations show that satellite‐estimated median w c is slightly greater than the RWP estimates, but they show solid agreement when compared at the 95th percentiles (intense updrafts). RWP‐derived and satellite‐estimated M c are broadly comparable in the lower and middle troposphere, with some differences in the upper troposphere due to differences in convective core sampling. A k ‐means cluster analysis of multiple years of w c data shows that convective characteristics are distinctly different among extratropical convection, tropical land convection, and tropical oceanic convection. Tropical land convection is significantly more intense and more variable than the oceanic counterpart. Plain Language Summary: Properly representing and parameterizing cumulus convection has long been a central task of the global climate models (GCMs), as GCM simulations are highly sensitive to the assumptions made in the cumulus parameterization schemes, resulting in large uncertainties in predicting the future climate change. At the heart of many of today's GCM convection parameterizations are convective vertical velocity ( w c ) and mass flux ( M c ). Yet, few global observations of these critical parameters are available at this time globally. To improve this situation, the authors developed a novel, satellite‐based method for estimating profiles of w c and M c . We first evaluate the satellite estimates against collocated ground‐based radar wind profiler (RWP) retrievals. RWP‐derived and satellite‐estimated w c and M c are found to be broadly comparable, and their agreement improves when differences in sampling and definitions of convective clouds are considered. A k ‐means cluster analysis of multiple years of satellite‐estimated w c data is performed to identify salient patterns related to the structure and global distributions of convective vertical velocity. Results show that convective characteristics are distinctly different among extratropical convection, tropical land convection, and tropical oceanic convection. Our ongoing work seeks to use this newly developed w c and M c data set to evaluate GCM cumulus parameterizations. Key Points: A novel, satellite‐based method was developed to retrieve profiles of convective vertical velocity ( w c ) and convective mass flux ( M c ) Comparisons with collocated ground‐based radar wind profiler observations show broad agreements A k ‐means cluster analysis shows that convective vertical velocity is distinctly different between tropical land and oceanic convection